Fate sticks with you: a field experiment on the anthropomorphism of God and beliefs in tempting fate - Leong, Jillian Wai Lam (Nanyang Technological University, 2024)
To tempt fate is to behave in an overconfident manner, such as prematurely celebrating a job promotion, or taking unnecessary risks by skydiving without a helmet. What makes people reluctant to tempt fate? Past research has indicated that the anthropomorphism of God (AoG) elicits beliefs in tempting fate (BTF). While these studies were intellectually informative, they relied heavily on self-reports with limited external validity. The present study aimed to address this concern with a field experiment in the naturalistic settings. Participants recruited at health screening centres in Singapore were experimentally reminded of high AoG or low AoG, depending on conditions. Then, they were prompted to choose a sticker to put on themselves. Some stickers contained statements that bragged about good health (e.g., jinxing stickers), whereas other stickers contained statements that suggested the importance of good health (e.g., non-jinxing stickers). We predicted that participants will be inclined to choose a non-jinxing sticker, more so in the high AoG condition and less so in the low AoG condition. Contrary to predictions, results showed that participants in high AoG condition were no more likely to choose the non-jinxing stickers than participants in the low AoG condition. These results suggest that AoG did not elicit BTF in a naturalistic setting. We discuss possibilities for null results.